2018
DOI: 10.1021/acs.joc.8b00325
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of β-Amino Boronate Peptidomimetics

Abstract: Herein, we describe the synthesis of novel β-amino boronate peptidomimetics from amphoteric α-borylaldehydes in the Ugi multicomponent reaction. A mild deprotection method provided the free and stable boronic acid forms of the target molecules, which display notable stability toward protodeborylation. Despite the presence of Lewis acidic boron, there is no evidence for hydrolysis of the adjacent amide via a 5- or 6-membered ring intermediate. This methodology should facilitate the development of libraries of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…Our studies go much beyond a singleton report on the use of a few free boronic acids in the Ugi reaction as we also investigated the GBB-3CR, UT-4CR, and several different IMCR variations more in an unprecedented breadth of building block combinations ( 35 , 36 ). In other reports, isocyanide-bearing boronic acids are only known in their protected ester form that would need another, often harsh, deprotecting step to yield boronic acids suitable for screening ( 39 , 40 ). Here, we found that IMCR generally runs under such mild conditions that free boronic acids are widely tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies go much beyond a singleton report on the use of a few free boronic acids in the Ugi reaction as we also investigated the GBB-3CR, UT-4CR, and several different IMCR variations more in an unprecedented breadth of building block combinations ( 35 , 36 ). In other reports, isocyanide-bearing boronic acids are only known in their protected ester form that would need another, often harsh, deprotecting step to yield boronic acids suitable for screening ( 39 , 40 ). Here, we found that IMCR generally runs under such mild conditions that free boronic acids are widely tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…Besides reduction with NaBH(OAc) 3 , iminium ion 31 could be engaged in the Ugi four‐component reaction (Scheme 21, eq. 2) [61] or a Strecker‐type transformation (Scheme 21, eq. 3) [62] to access β‐amino MIDA boronates.…”
Section: Methods For the Synthesis Of β‐Aminoalkylboronic Acid Derivativesmentioning
confidence: 99%
“…Said review attested to the rapid development in the field, with most of the protocols having been reported in the literature over the last decade. Even if major advances regarding the synthetic accessibility of such derivatives have been made, most of the reported strategies still rely on multi-step sequences, though there is a single example of a multicomponent strategy [15]. Owing to their ability to construct highly functionalized molecular scaffolds from simple precursors in a single step, multicomponent reactions (MCRs) can be considered excellent tools for diversity-oriented synthesis applications in the drug discovery field [16].…”
Section: Introductionmentioning
confidence: 99%